Finite element analysis and programming : an introduction - Shivaswamy, Shashishekar ([S.l.] : Alpha Science Intl Ltd, 2010)
Finite Element Analysis is a widely used technique in many engineering disciplines. Implementing the principles of FEA through programming is crucial for a thorough understanding of the subject. In this book, the concepts of FEA and its programming is illustrated uniquely in a transparent manner using the math package MATHCAD. The details in programming, with solution at various intermediate stages, are discussed for numerous elements with fully functional codes. Programs in Microsoft Excel using VBA are also presented. The book provides many challenging problems and programming assignments.